IMPLEMENTASI KEBIJAKAN PENYEBARLUASAN INFORMASI PENYELENGGARAAN PEMERINTAHAN DI KOTA BEKASI MELALUI BEKASI ICONIC - Adi Susila; Leni Yunaida; Dila Novita (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
Electronic Government in Indonesia has been introduced and started through Presidential Instruction No. 3 of 2003 concerning the National Policy and Strategy for Electronic Government Development which states that the development of electronic government is an effort to develop governance based on using electronics in order to improve the quality of public services effectively and efficiently. Besides that, e-government also aims to support good governance (good governance). The purpose of this research is to analyze the implementation of Mayor Regulation Number 32 of 2019 concerning the Dissemination of Information on Government Administration in the Bekasi City Government Environment in the Bekasi Iconic Application, identify the inhibiting factors for implementing the Bekasi Iconic Application, analyze any efforts to overcome obstacles in implementation, and find out the perceptions of the community concerned the application. Researchers examined this matter using a constructivism paradigm with qualitative research methods accompanied by a case study research approach. Based on the results of the research, the implementation of Mayor Regulation Number 32 of 2019 concerning Dissemination of Government Information in the Bekasi City Government Environment through the Bekasi Iconic Application which was launched in 2018 did not run optimally due to several obstacles in its implementation, the main of these obstacles is the lack of coordination between organizations Regional Apparatus (OPD) related to updating existing systems in each OPD, how to overcome obstacles by coordinating and monitoring between Regional Apparatus regarding updating application data of each Regional apparatus collected in Bekasi Iconic, the community hopes for continuous quality improvement towards The Bekasi Iconic application is a collaboration of information between OPDs around the Bekasi City government to maximize the implementation of public information services for the people of Bekasi City.